TINDAK TUTUR DIREKTIF PADA PEMBELAJARAN BAHASA INDONESIA KELAS XI MA HIDAYATUL MUTA’ALLIMIN DATINAWONG BABAT - Mufarikhatul Izza; Sutardi; Mustofa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesian language learning takes place through interactions between teachers and students producing various forms of speech acts, one of which is directive speech acts which function to direct the interlocutor to carry out the expected action. This research aims to describe the form and function of directive speech acts in Indonesian language learning in class XI MA Hidayatul Muta'allimin Datinawong Babat. The approach used in this research is descriptive qualitative, with data sources in the form of speech produced by teachers and students during learning activities. The research data is in the form of speech containing directive speech acts, which are collected through observation, listening, recording and note-taking techniques. Research instruments include observation sheets, cell phones as recording devices, and data corpus sheets. Data was analyzed descriptively through identification, classification and interpretation stages based on the context of use. The research results show that directive speech acts are realized in three forms, namely news sentences (declarative), question sentences (interrogative), and command sentences (imperative). The form of a news sentence has six functions, namely requesting, asking, ordering, prohibiting, agreeing and suggesting. The interrogative sentence form has three functions, namely requesting, questioning, and commanding, while the command sentence form has four functions, namely requesting, ordering, prohibiting, and suggesting.Keywords: Speech Acts, Directive, Form, Function, in the learning process.